Predictors of annual prostate-specific antigen (PSA) screening among black men: results from an urban community-based prostate cancer screening program - Marquita W. Lewis-Thames; Saira Khan; Veronica Hicks; Bettina F. Drake (Journal of Men's Health, 2021)
Background and objective: Black men have an increased risk of prostate cancer mortality compared with any racial or ethnic group. Further, research on prostate cancer prevention and control messaging focusing on Black men is limited. Community screening events are successful in attracting members from high-risk groups, like Black men, and are a valuable source to collect cancer screening and health promotion data. Therefore, the authors examined data of Black men attending a community-based PCa screening event to evaluate predictors of annual PCa screening, and identify sub-populations of Black men needing targeted cancer prevention messaging. Methods: Black men attending PCa screening events in St. Louis, MO 2007–2017 were eligible. Participants completed either a mail-in or on-site survey at the time of their screening to collect information on annual screening history. We analyzed sociodemographic factors, having a first-degree relative with a history of PCa, healthcare utilization characteristics, and predictors of annual PSA screening. Logistic regression analysis was used to assess the association between predictors and annual PSA screening. Results: Data was analyzed from 447 respondents. One-third of the residents did not know their cancer family history status. Older age and having a primary healthcare provider predicted an annual prostate cancer after attending the PCa community screening event. In the fully adjusted model, all ages older than 45 years were 2–4 times more likely to have an annual PCa screening. Having a healthcare provider also predicted an annual PCa screening (OR: 4.59, 95% CI: 2.30–9.14). Conclusion: Regardless of sociodemographic and family history factors, older Black men and those with a primary physician are more likely to have an annual PSA screening. Cancer prevention promotion efforts for Black men should target mechanisms that facilitate family cancer history conversations to engage younger Black men. Also, additional health promotions efforts are needed to educate Black men without a primary healthcare provider.